2021
DOI: 10.1002/ieam.4510
|View full text |Cite
|
Sign up to set email alerts
|

Realistic exposure of the fungicide bixafen in soil and its toxicity and risk to natural earthworm populations after multiyear use in cereal

Abstract: A comprehensive multiyear monitoring program was conducted to assess the exposure, effects, and long-term risk of the fungicide bixafen to earthworms in cereal fields. The realistic exposure of bixafen in soil was assessed at 10 representative field sites in Germany after a period of up to 8 years of use with five different products containing bixafen, followed by annual measurements from 2017 to 2019. The measured exposure concentrations were compared with modeled predicted environmental concentrations in soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…(2019) exceeded the maximum individual worm weight used in the zero-variate data ( Table 1 ; Lofs-Holmin, 1983) and other studies (e.g. Ernst et al ., 2022 ). We thus allowed the scaled functional response for this experiment to exceed a maximum value of 1.…”
Section: Discussionmentioning
confidence: 65%
“…(2019) exceeded the maximum individual worm weight used in the zero-variate data ( Table 1 ; Lofs-Holmin, 1983) and other studies (e.g. Ernst et al ., 2022 ). We thus allowed the scaled functional response for this experiment to exceed a maximum value of 1.…”
Section: Discussionmentioning
confidence: 65%
“…From this work, median effect concentration (EC 50 ) values for total earthworm abundance at one and 12 months after application were defined as 1.089 and 9.441 kg a.i./ha, respectively. Other studies (Daniels et al, 2020;Ernst et al, 2021) also found effects in the field at rates that ranged from 6 to 10 kg carbendazim/ha.…”
Section: Risk Assessment Scheme Validation and Risk Triggersmentioning
confidence: 84%